Redox Homeostasis in Plants under Abiotic Stress: Role of electron carriers, energy metabolism mediators and proteinaceous thiols - Dhriti Kapoor; Resham Sharma; Neha Handa; Harpreet Kaur; Amandeep Rattan; Poonam Yadav; Vandana Gautam; Ravdeep Kaur; Renu Bhardwaj (Frontiers in Environmental Science, 2015)
Contemporaneous presence of both oxidized and reduced forms of electron carriers is mandatory in efficient flux by plant electron transport cascades. This requirement is considered as redox poising that involves the movement of electron from multiple sites in respiratory and photosynthetic electron transport chains to molecular oxygen. This flux triggers the formation of superoxide, consequently give rise to other reactive oxygen species (ROS) under adverse environmental conditions like drought, high or low temperature, heavy metal stress etc. that plants owing during their life span. Plant cells synthesize ascorbate, an additional hydrophilic redox buffer, which protect the plants against oxidative challenge. Large pools of antioxidants also preside over the redox homeostasis. Besides, tocopherol is a liposoluble redox buffer, which efficiently scavenges the ROS like singlet oxygen. In addition, proteinaceous thiol members such as thioredoxin, peroxiredoxin and glutaredoxin, electron carriers and energy metabolism mediators phosphorylated (NADP) and non-phosphorylated (NAD+) coenzyme forms interact with ROS, metabolize and maintain redox homeostasis.